The expected impact of IFRS 16 leases: evidence from companies listed on the portuguese stock exchange - Lima, Jéssica (2021)
Purpose: The International Financial Reporting Standard (IFRS) 16 – Leases, is mandatory since January 2019, replacing the current standard International Accounting Standard (IAS) 17. This new standard requires the accounting of operating leases in the lessee’s balance sheet, recognizing a right-of-use asset and the corresponding liability. The aim of this paper is to analyze the potential effects of IFRS 16 on financial statements and their impacts on financial indicators, as well as the way in which the transition to the new standard will be made. Methodology: Content analysis of 2018 reports and accounts from a sample of Portuguese listed companies, in order to analyze the financial impact of capitalizing off-balance lease. In relation to the financial structure ratios analyzed, we have compared the values existing in 2018, before the adoption of IFRS 16, with those predicted after its adoption. Originality: This paper contributes to ongoing international debate and research concerning lease-accounting, by providing empirical evidence in our country, Portugal, where existing studies are still scarce. Findings: Our results allowed us to conclude that the majority of the companies in the sample (84%) will adopt the modified retrospective transition option, while the rest (16%) will adopt the full retrospective transition, in which case it is mandatory to re-express the comparative information. Regarding the impact of the new standard on the financial statements’ elements, we have concluded that assets and liabilities will increase, while equity will decrease, consequently affecting the balance sheet. Regarding the income statement, the results reveal the decrease in supplies and external services, which will allow an increase in EBITDA. On the other hand, there is an increase in financial and amortization/depreciation expenses. After comparing the financial indicators, between 2017 and 2018, it is expected that the debt ratio will increase, while the financial autonomy and solvency ratios will decrease. We have confirmed that the sector of activity most affected by IFRS 16 will be the retail sector and that the sector of basic resources is the one that will experience the least impact. Practical implications: The capitalization of lease accounting has implications on levels of indebtedness and performance measures. The lease-accounting regulatory change can affect the investors decisions and the managers’ behavior, concerning the financing decisions and earning management. This paper findings can help lessors, preparers and analysts to understand the expected impact of the implementation of IFRS 16.